2021
DOI: 10.1021/acsaem.1c01658
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Dielectric and Energy Storage Performance of PVDF-Based Relaxor Ferroelectrics with Hydrogen Bonds

Abstract: Polymer-based dielectrics with high energy density and low dielectric loss are urgently needed in microelectronic equipment and high-power density electric energy storage devices. In an effort to overcome the disadvantage of the high energy loss of poly­(vinylidene fluoride) (PVDF)-based ferroelectric fluoropolymers, herein, a series of poly­(vinylidene fluoride-co-trifluoroethylene-co-chlorotrifluoroethylene)-g-poly­(vinyl alcohol) [P­(VTrCT)-g-PVA] were fabricated using the reversible addition–fragmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Apart from the above-mentioned techniques, there are also some other techniques that are reported to be useful in augmenting the energy storage features of PVDF-based devices. Zhang et al [165] fabricated poly(vinylidene fluoride-cotrifluoroethylene-co-chlorotrifluoroethylene)-g-poly(vinyl alcohol) [P-(VTrCT)-g-PVA] composites where the energy storage performance was improved via the hydrogen bonding between [47] (Reproduced with permission from Ref. [47].…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the above-mentioned techniques, there are also some other techniques that are reported to be useful in augmenting the energy storage features of PVDF-based devices. Zhang et al [165] fabricated poly(vinylidene fluoride-cotrifluoroethylene-co-chlorotrifluoroethylene)-g-poly(vinyl alcohol) [P-(VTrCT)-g-PVA] composites where the energy storage performance was improved via the hydrogen bonding between [47] (Reproduced with permission from Ref. [47].…”
Section: Methodsmentioning
confidence: 99%
“…In the previous section, it was introduced that the same research group prepared a series of P(VDF-TrFE-CTFE)-g-PVA using RAFT procedure. And H-bond could be constructed among the -OH and ester groups, which is responsible for the suppressed ferroelectric loss and enhanced E b and thus improved U e and η (Zhang et al, 2021). Wang R. et al (2022) reported a kind of all-organic ultrahighenergy-density dielectric composites materials consisting of ferroelectric polymer P(VDF-HFP) and glucose, exhibiting record U e (37.7 J/cm 3 ) that outperforms the state-of-the-art dielectric polymer composites.…”
Section: Hydrogen Bond and Cross-linked Structuresmentioning
confidence: 99%
“…In addition, Zhicheng Zhang’s group fabricated a series of P(VDF-TrFE-CTFE)- g -PVA with high U e and low dielectric loss for using RAFT procedure ( Zhang et al, 2021 ). The PVA side chain shows great compatibility with the PVDF main chain and the hydrogen bond could be constructed among the hydroxyl and ester groups, which is responsible for the suppressed ferroelectric loss and enhanced E b and thus improved U e and η .…”
Section: Controllable Synthesis Of All-organic Polymer Dielectricmentioning
confidence: 99%
See 1 more Smart Citation
“…3 As suggested by the equation E b = 0.6( Y / ε 0 ε r ) 0.5 , where Y is Young's modulus, Y has a dominant effect on E b and thus U e . 18 Many glassy polymers with high T g and Y have been developed and tested for dielectric films during the past few years. Cao's group synthesized a series of dipolar relaxation enhanced cyclic olefins with a U e of ∼9 J cm −3 , an E b of ∼750 MV m −1 and rather high T g (∼178 °C).…”
Section: Introductionmentioning
confidence: 99%